Three-dimensional crosslinked structure, active energy ray curable resin composition, paint, coating film, lens, and method for producing three-dimensional crosslinked structure

A three-dimensional crosslinked structure using controlled radical polymerization addresses the solvent and viscosity issues of ultraviolet-curable acrylic acrylate polymers, offering flexible and scratch-resistant coatings and lenses.

JP7600544B2Active Publication Date: 2024-12-17DIC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020092218
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-27
Publication Date
2024-12-17
Estimated Expiration
2040-05-27

AI Technical Summary

Technical Problem

Existing ultraviolet-curable acrylic acrylate polymers require large amounts of organic solvents, leading to environmental impact and increased viscosity, limiting their use in coatings and lenses, and lack sufficient scratch resistance and flexibility, especially for curved and flexible substrates.

Method used

A three-dimensional crosslinked structure is developed, comprising linear polymers with acrylic groups extending from a core, synthesized through controlled radical polymerization, allowing low viscosity without solvents and providing flexibility and scratch resistance.

Benefits of technology

The three-dimensional crosslinked structure achieves low viscosity, minimal mold shrinkage, and excellent flexibility and scratch resistance, making it suitable for coatings and lenses with reduced solvent use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600544000002
    Figure 0007600544000002
  • Figure 0007600544000001
    Figure 0007600544000001
Patent Text Reader

Abstract

To provide a polymer which has such low viscosity as to use little organic solvent when being formed into an ultraviolet curable resin composition for protective coating and optical lens manufacture, has small molding shrinkage when being formed into a coated film and a lens, and has good flexibility and scratch resistance.SOLUTION: A three-dimensional crosslinked structure has a plurality of linear polymers that are copolymers or block polymers. The linear polymer has one or more acrylic groups, and a core part is formed by aggregation and chemical bonding of one ends of the plurality of linear polymers. It is preferable to have a halogen group or a functional group including a thiocarbonylthio structure in the one end of the linear polymer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a three-dimensional crosslinked structure, an active energy ray-curable resin composition, a coating material, a coating film, a lens, and a method for producing the three-dimensional crosslinked structure. [Background technology]

[0002] UV-curable resins have the characteristic of being polymerized and cured in a short time by irradiation with UV rays, and are therefore used in applications such as protective coatings for electronic devices such as smartphones and the exterior and interior of automobiles, and optical lenses, and are expected to continue to grow in the future. UV-curable resin compositions are mainly composed of polymers, monomers, and photopolymerization initiators, and UV-curable acrylic acrylate polymers are often used as the polymer because they provide flexibility that is not sufficient with monomers alone and can reduce cure shrinkage. The use of UV-curable acrylic acrylate polymers as paints for protective coating applications such as hard coats is described, for example, in Patent Document 1 below.

[0003] Polymers such as the above UV-curable acrylic acrylate polymers have a large molecular weight, so they must be diluted with an organic solvent when applied. The use of a large amount of organic solvents places a heavy burden on the environment, so there is a demand for reducing the amount of organic solvents used when using UV-curable acrylic acrylate polymers.

[0004] In paints containing polymers such as the above-mentioned UV-curable acrylic acrylate polymers, simply reducing the amount of organic solvent increases the viscosity, making the paint impossible to coat, and so it is necessary to reduce the viscosity of the polymer itself.

[0005] Furthermore, in the fields of protective coatings for electronic devices and optical lenses, even higher scratch resistance is required. Furthermore, in recent years, materials with small cure shrinkage and flexibility are required for protective coatings on curved and flexible substrates such as film-type displays.

[0006] However, polymers synthesized by conventional free radical polymerization have an amorphous structure, which limits the ability to reduce viscosity. Other polymers include gel-crosslinked star polymers produced by anionic polymerization and dendrimers with a structure that branches regularly from the center. However, conventional star polymers cannot directly introduce polar groups (such as hydroxyl groups) and require protection and deprotection, making it difficult to synthesize UV-curable polymers. In addition, although dendrimers have a highly regular structure, they have problems with flexibility and molding shrinkage when used in the fields of protective coatings and optical lenses. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2011-207947 A Summary of the Invention [Problem to be solved by the invention]

[0008] As described above, in the field of protective coatings and optical lenses, new polymers are required as polymers to be used in ultraviolet curable resin compositions. Therefore, the problem to be solved by the present invention is to provide a polymer that has a low viscosity so that organic solvents are hardly used when it is used as an ultraviolet curable resin composition for producing protective coatings or optical lenses, and has small molding shrinkage and good flexibility and scratch resistance when it is used as a coating film or lens. [Means for solving the problem]

[0009] As a result of intensive research into solving the above-mentioned problems, the inventors have found that the above-mentioned problems can be solved by using a three-dimensional crosslinked structure having a specific structure in which a plurality of linear polymers extend radially from a core portion, and have completed the present invention.

[0010] That is, the present invention relates to the following. Item 1. A three-dimensional crosslinked structure having a plurality of linear polymers which are copolymers or block polymers, each of which has one or more acrylic groups, and in which one end of each of the plurality of linear polymers is assembled and chemically bonded to form a core portion. Item 2. The three-dimensional crosslinked structure according to Item 1, wherein one end of the linear polymer has a functional group containing a halogen group or a thiocarbonylthio structure. Item 3. The three-dimensional crosslinked structure according to Item 1 or 2, wherein a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) is 1.1 to 3.0. Item 4. An active energy ray-curable resin composition comprising the three-dimensional crosslinked structure according to any one of items 1 to 3. Item 5. A coating material comprising the active energy ray-curable resin composition according to item 4. Item 6. A coating film which is a cured product of the active energy ray-curable resin composition according to item 4. Item 7. A lens which is a cured product of the active energy ray-curable resin composition according to item 4. Item 8. A method for producing a three-dimensional crosslinked structure, comprising the steps of: polymerizing a linear polymer that is a copolymer or block polymer having an active hydrogen functional group; chemically bonding one end of a plurality of the linear polymers to form a core portion; and converting the active hydrogen functional group of the linear polymer to an acrylic group. Effect of the Invention

[0011] The active energy ray curable resin composition containing the cured product of the three-dimensional crosslinked structure of the present invention has a low viscosity when used as a paint, so that organic solvents are hardly used, and when cured to form a coating film or lens, the molding shrinkage is small, and the cured product has excellent flexibility, transparency, and scratch resistance. Therefore, the active energy ray curable resin composition is suitable as a paint for protective coating applications such as hard coats, and as an optical lens used in mobile terminals such as smartphones. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of a three-dimensional crosslinked structure of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [3D crosslinked structure] The three-dimensional crosslinked structure of the present invention has a plurality of linear polymers (arm polymers) which are copolymers or block polymers, the linear polymers having one or more acrylic groups (acryloyl groups), and one end of the plurality of linear polymers is assembled and chemically bonded to form a core (central core). In the specification of the present invention, "one end" has the above meaning. The "end" in "one end" of the linear polymer does not mean only the end, but is a concept including the vicinity of the end. A structure which is one embodiment of the three-dimensional crosslinked structure of the present invention is shown in FIG. 1.

[0014] Although there are no particular limitations, the three-dimensional crosslinked structure of the present invention is preferably produced by controlled radical (living radical) polymerization, including the synthesis of linear polymers. In particular, it is preferably produced by ATRP (Atom Transfer Radical Polymerization) or RAFT polymerization (Reversible Addition / Fragmentation Chain Transfer Polymerization). Controlled radical (living radical) polymerization such as ATRP and RAFT polymerization allows polymerization to proceed linearly while preventing recombination and disproportionation of growing radicals, allowing precise synthesis of polymers with a narrow molecular weight distribution and a high chain end functional group ratio.

[0015] The linear polymer (arm polymer) is represented by lines extending radially from a core (central nucleus) in the schematic diagram of FIG. 1. The number average molecular weight (Mn) of the linear polymer is, for example, in the range of 1,000 to 200,000, and preferably in the range of 2,000 to 100,000. The linear polymer preferably has a monomer skeleton of a (meth)acrylic compound having no active hydrogen functional group and a (meth)acrylic compound having an active hydrogen functional group. Examples of the active hydrogen functional group include a hydroxyl group, a carboxyl group, and an amino group.

[0016] Examples of (meth)acrylic compounds that do not have an active hydrogen functional group include (meth)acrylic acid esters having an alkyl chain, such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate. Examples of (meth)acrylic compounds that have an active hydrogen functional group include (meth)acrylic acid alkyl esters having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate, polyethylene glycol monoacrylate, polypropylene glycol monoacrylate, (meth)acrylic acid, (meth)acrylamide, and (meth)acrylimide. Examples of compounds that do not have an active hydrogen functional group include styrene and styrene derivatives, acrylonitrile, and the like, in addition to (meth)acrylic compound f.

[0017] Among these, methyl methacrylate and 2-hydroxyethyl methacrylate are preferred from the viewpoints of availability and polymerizability. The linear polymer may be any of a block copolymer, an alternating copolymer, and a random polymer. The linear polymer may have a side chain to an extent that does not impair the effects of the present invention. The linear polymer may have a functional group such as an alkyl group or an ether group as a functional group other than an acrylic group. The number of linear polymers (arm polymers) in the three-dimensional crosslinked structure of the present invention is, for example, 3 to 500, and preferably 6 to 350.

[0018] In the core (central core) of the three-dimensional crosslinked structure of the present invention, one end of the linear polymer is preferably chemically bonded directly or via another chemical structure to have a gel-like amorphous structure. The chemical bond may be either a covalent bond or an ionic bond. One end of the linear polymer may be reacted with a multifunctional reactive compound such as a divinyl compound to form the above-mentioned chemical bond. The core may also have a linear polymer that bundles the radially extending linear polymers. The three-dimensional crosslinked structure of the present invention has a flexible structure by having a gel-like amorphous structure in the core, and when it is made into a coating film after curing, it has excellent abrasion resistance while maintaining transparency.

[0019] One end of the linear polymer may have a functional group containing a thiocarbonylthio structure (S=CS) derived from a chain transfer agent (RAFT agent) when synthesized by RAFT polymerization. In addition, one end of the linear polymer may have a functional group containing a halogen group derived from an organic halogen compound that is a polymerization initiator when polymerized by ATRP. Examples of the halogen group include a chloro (Cl) group, a bromo (Br) group, and an iodine (I) group. Examples of the functional group containing a halogen group include a bromoisopropyl group.

[0020] The three-dimensional crosslinked structure of the present invention has a number average molecular weight (Mn) of, for example, 5,000 to 300,000, preferably 7,000 to 200,000. The weight average molecular weight (Mw) is, for example, 5,000 to 600,000, preferably 10,000 to 400,000. The ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is preferably in the range of 1.1 to 3.0, more preferably in the range of 1.1 to 2.5, and even more preferably in the range of 1.1 to 2.0. When Mw / Mn is in the above range, the molecular weight distribution is narrow, and as a result, the viscosity can be reduced.

[0021] In the present invention, the number average molecular weight (Mn) and the weight average molecular weight (Mw) are values ​​measured using gel permeation chromatography (GPC) under the following conditions.

[0022] Measuring device: Tosoh Corporation HLC-8220 Column: Tosoh Corporation guard column HXL-H + Tosoh Corporation TSKgel G5000HXL + Tosoh Corporation TSKgel G4000HXL +Tosoh Corporation TSKgel G3000HXL + Tosoh Corporation TSKgel G2000HXL Detector: RI (differential refractometer) Data processing: Tosoh Corporation SC-8010 Measurement conditions: Column temperature 40℃ Solvent Tetrahydrofuran Flow rate 1.0ml / min Standard: Polystyrene Sample: 100 μl of tetrahydrofuran solution containing 0.5% by mass of resin solids filtered through a microfilter

[0023] The gel particle size (D50) in the three-dimensional crosslinked structure of the present invention is, for example, 5 to 100 nm, preferably 5 to 50 nm, and more preferably 5 to 30 nm. When the gel particle size is within this range, the three-dimensional crosslinked structure has a microstructure, which reduces the viscosity. The gel particle size can be calculated, for example, by preparing a 1% by mass tetrahydrofuran solution of the three-dimensional crosslinked structure in terms of resin solid content, and measuring the solution with a dynamic light scattering particle size distribution analyzer.

[0024] [Method of manufacturing 3D crosslinked structures] The three-dimensional crosslinked structure of the present invention is obtained by a method including a step of polymerizing a linear polymer that is a copolymer or block polymer having an active hydrogen functional group (linear polymer polymerization step), a step of chemically bonding one end of a plurality of linear polymers to form a core portion (core formation step), and a step of converting the active hydrogen functional group of the linear polymer to an acrylic group (acrylic group conversion step). In particular, the linear polymer polymerization step is preferably carried out by RAFT polymerization or ATRP, which are types of controlled radical (living radical) polymerization. Note that the three-dimensional crosslinked structure of the present invention is not limited to that obtained by the method described in the present specification.

[0025] In RAFT polymerization, a reaction related to RAFT equilibrium is added to the general free radical polymerization of substituted monomers, and the polymerization reaction proceeds by a reversible chain transfer reaction via a chain transfer agent (RAFT agent). As the chain transfer agent (RAFT agent) used in RAFT polymerization, it is preferable to use thiocarbonylthio compounds such as dithioesters, dithiocarbamates, trithiocarbonates, and xanthates, and halogen compounds having a chloro (Cl) group, a bromo (Br) group, or an iodine (I) group. Examples of the chain transfer agent (RAFT agent) include 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid, 2-cyano-2-propyl benzodinionate, cyanomethyl methyl(1-phenyl)carbodithiodionate, 4-cyano-4-(phenylcarbothiolino)pentanoic acid, 2-cyano-2-propyl dodecyl trithiocarbonate, 2-(dodecylthiocarbanothiolino)-2-methylpropionic acid, and cinanomethyl dodecyl trithiocarbonate. Examples of the chain transfer agent (RAFT agent) include commercially available reagents manufactured by Sigma-Aldrich, Tokyo Chemical Industry Co., Ltd., and Fujifilm Wako Pure Chemical Industries, Ltd. The chain transfer agent (RAFT agent) can be selected appropriately according to the monomer.

[0026] In ATRP, an organic halogen compound is used as a polymerization initiator, and a transition metal complex such as a copper(I) complex is used as a catalyst. In ATRP, the carbon-halogen bond of the organic halogen compound is radically cleaved, the halogen atom moves to the metal atom of the catalyst, and the radical of the initiator is added to the double bond of the vinyl monomer. The newly generated radical active species becomes a dormant species by abstracting the halogen atom from the metal atom of the catalyst. The radical active species and the dormant species are in equilibrium, but the equilibrium is heavily biased toward the dormant species, and the terminal of the radical active species present in low concentration is added to the vinyl monomer, causing the polymer to grow. As the organic halogen compound used as the polymerization initiator, 2-bromoisobutyric acid ethyl, 2-bromo-2-methylpropionyl bromide, 2-BOC-2-bromopropane, 2-bromo-2-methylpropionate ethyl, etc. can be used. In addition, examples of catalysts that can be used include copper chloride (I), copper chloride (II), copper bromide (I), copper bromide (II), chloro(indenyl)bis(triphenylphosphine)ruthenium(II) (dichloromethane adduct), and chloro(η5-pentamethylcyclopentadiene)[bis(triphenylphosphine)]ruthenium(II). Commercially available reagents from Sigma-Aldrich, Tokyo Chemical Industry, Fujifilm Wako Pure Chemical Industries, and other companies can be used as these organic halogen compounds and catalysts.

[0027] In the linear polymer polymerization process, for example, a monomer such as methyl methacrylate (MMA) or hydroxymethyl acrylate (HEMA) is heated in the presence of a solvent and polymerized by precise radical polymerization such as the above-mentioned RAFT polymerization or ATRP, thereby obtaining a linear polymer as a copolymer or block polymer.

[0028] As described above, the linear polymer preferably has a monomer skeleton of a (meth)acrylic compound having no active hydrogen functional group and a (meth)acrylic compound having an active hydrogen functional group. Examples of the active hydrogen functional group include a hydroxyl group, a carboxyl group, and an amino group. It is preferable to obtain a linear polymer having an active hydrogen functional group by using a monomer having an active hydrogen functional group in the linear polymer polymerization step. However, an active hydrogen functional group may be introduced into one end of the linear polymer after polymerization.

[0029] In the core formation step, a reaction is carried out to chemically bond one end of a linear polymer. The reaction is carried out by reacting a polyfunctional reactive compound, which is a divinyl compound such as ethylene glycol dimethacrylate (EGDMA), in the presence of a radical initiator such as 2,2'-azobis(2-methylbutyronitrile) or azobisisobutyronitrile. The reaction can be carried out, for example, by introducing nitrogen at room temperature to deoxidize, then raising the temperature in the system to 50 to 100°C while stirring, and maintaining the temperature at 50 to 100°C for 5 to 24 hours.

[0030] After the core is formed, in the process of converting the active hydrogen functional group to an acrylic group (acrylic group conversion process), an isocyanate group-containing vinyl compound, for example, 2-isocyanatoethyl acrylate, methacryloyloxyethyl isocyanate, 、( Meth)acryloyl isocyanate 、1 The active hydrogen functional group is converted to an acrylic group by reacting with an isocyanate group-containing vinyl compound such as 1-(bisacryloyloxymethyl)ethyl isocyanate, or (meth)acrylic acid chloride, (meth)acrylic acid anhydride, or (meth)acrylic acid. The reaction can be carried out by dissolving the material to be the three-dimensional crosslinked structure in methyl ethyl ketone or the like to prepare a solution, adding an isocyanate group-containing vinyl compound, and heating the system to 50 to 100°C with stirring in the presence of an inorganic metal catalyst, and maintaining the system at 50 to 100°C for 1 to 8 hours. In this manner, the three-dimensional crosslinked structure of the present invention is obtained.

[0031] [Active energy ray curable resin composition] The active energy ray curable resin composition of the present invention is not particularly limited as long as it contains the above-mentioned three-dimensional crosslinked structure, but it is preferable that it contains a polyfunctional vinyl compound to crosslink the three-dimensional crosslinked structure. By crosslinking the three-dimensional crosslinked structure using the polyfunctional vinyl compound in this way, it is possible to obtain the effects of low viscosity, small molding shrinkage in the cured product, and good flexibility and scratch resistance.

[0032] The polyfunctional vinyl compound preferably has 2 to 6 vinyl groups in one molecule. Examples of compounds having two vinyl groups (bifunctional monomers) include tripropylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol hydroxypivalic acid ester di(meth)acrylate, hydroxypivalic acid neopentyl glycol ester di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, acrylate, 1,9-nonanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, caprolactone-modified hydroxypivalic acid neopentyl glycol ester di(meth)acrylate, propoxylated neopentyl glycol di(meth)acrylate, ethoxy-modified bisphenol A di(meth)acrylate, polyethylene glycol 200 di(meth)acrylate, polyethylene glycol 400 di(meth)acrylate, and methylene bisacrylamide.

[0033] Examples of compounds having three vinyl groups (trifunctional monomers) include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, triallyl isocyanate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, and propoxylated glyceryl tri(meth)acrylate.

[0034] Examples of compounds having four or more vinyl groups include pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol hydroxypenta(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, penta(meth)acrylate ester, and dipentaerythritol hexa(meth)acrylate. These polyfunctional vinyl compounds may be used alone or in combination of two or more. In addition, a compound having one vinyl group (monofunctional monomer) may be used in combination with the polyfunctional vinyl compound.

[0035] The content of the polyfunctional vinyl compound is, for example, 1 to 500 parts by weight, preferably 2 to 100 parts by weight, relative to 100 parts by weight of the three-dimensional crosslinked structure. When crosslinking is performed with the polyfunctional vinyl compound, a radical polymerization initiator such as 2,2'-azobis(2-methylbutyronitrile) (AMBN) or t-butylperoxy-2-ethylhexanoate ("Perbutyl O" manufactured by NOF Corporation) may be used.

[0036] The active energy ray-curable resin composition of the present invention may contain, in addition to the polyfunctional vinyl compound, an organic solvent, an ultraviolet absorber, an antioxidant, a silicon-based additive, a fluorine-based additive, an antistatic agent, a silane coupling agent, organic beads, inorganic fine particles, inorganic fillers, a rheology control agent, a defoaming agent, an antifogging agent, a colorant, and the like, as necessary.

[0037] Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; cyclic ether solvents such as tetrahydrofuran and dioxolane; esters such as methyl acetate, ethyl acetate, and butyl acetate; aromatic solvents such as toluene and xylene; alcohol solvents such as carbitol, cellosolve, methanol, isopropanol, butanol, and propylene glycol monomethyl ether; and glycol ether solvents such as ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monopropyl ether. These organic solvents may be used alone or in combination of two or more.

[0038] The organic solvent is used mainly for the purpose of adjusting the viscosity of the active energy ray curable resin composition, and is usually preferably adjusted so that the non-volatile content is in the range of 30 to 90 mass %. Since the active energy ray curable resin composition of the present invention has a relatively low viscosity, the amount of organic solvent used can be reduced compared to a typical acrylic acrylate monomer having a large molecular weight.

[0039] Examples of the ultraviolet absorber include triazine derivatives such as 2-[4-{(2-hydroxy-3-dodecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-{(2-hydroxy-3-tridecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-(2'-xanthenecarboxy-5'-methylphenyl)benzotriazole, 2-(2'-o-nitrobenzyloxy-5'-methylphenyl)benzotriazole, 2-xanthenecarboxy-4-dodecyloxybenzophenone, and 2-o-nitrobenzyloxy-4-dodecyloxybenzophenone.

[0040] Examples of the antioxidant include hindered phenol-based antioxidants, hindered amine-based antioxidants, organic sulfur-based antioxidants, and phosphate-based antioxidants.

[0041] Examples of the silicon-based additive include polyorganosiloxanes having an alkyl group or a phenyl group, such as dimethylpolysiloxane, methylphenylpolysiloxane, cyclic dimethylpolysiloxane, methylhydrogenpolysiloxane, polyether-modified dimethylpolysiloxane copolymer, polyester-modified dimethylpolysiloxane copolymer, fluorine-modified dimethylpolysiloxane copolymer, and amino-modified dimethylpolysiloxane copolymer, polydimethylsiloxanes having a polyether-modified acrylic group, and polydimethylsiloxanes having a polyester-modified acrylic group.

[0042] The fluorine-based additives include, for example, the "Megafac" series manufactured by DIC Corporation.

[0043] Examples of the organic beads include polymethyl methacrylate beads, polycarbonate beads, polystyrene beads, polyacrylic styrene beads, silicone beads, glass beads, acrylic beads, benzoguanamine resin beads, melamine resin beads, polyolefin resin beads, polyester resin beads, polyamide resin beads, polyimide resin beads, polyethylene fluoride resin beads, polyethylene resin beads, etc. The average particle size of these organic beads is preferably in the range of 1 to 10 μm.

[0044] Examples of the antistatic agent include pyridinium, imidazolium, phosphonium, ammonium, or lithium salts of bis(trifluoromethanesulfonyl)imide or bis(fluorosulfonyl)imide.

[0045] The amount of the above additives used is preferably within a range in which the additives sufficiently exert their effects and do not inhibit ultraviolet curing. Specifically, the additives are each preferably used in an amount of 0.1 to 10 parts by mass in the active energy ray-curable resin composition of the present invention.

[0046] The active energy ray-curable resin composition of the present invention preferably further contains a photopolymerization initiator. Examples of photopolymerization initiators include various benzophenones such as benzophenone, 3,3'-dimethyl-4-methoxybenzophenone, 4,4'-bisdimethylaminobenzophenone, 4,4'-bisdiethylaminobenzophenone, 4,4'-dichlorobenzophenone, Michler's ketone, and 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone; xanthones and thioxanthones such as xanthone, thioxanthone, 2-methylthioxanthone, 2-chlorothioxanthone, and 2,4-diethylthioxanthone; various acyloin ethers such as benzoin, benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether; α-diketones such as benzyl and diacetyl; sulfides such as tetramethylthiuram disulfide and p-tolyl disulfide; and various benzoic acids such as 4-dimethylaminobenzoic acid and ethyl 4-dimethylaminobenzoate.3,3′-Carbonyl-bis(7-diethylamino)coumarin, 1-Hydroxycyclohexyl phenyl ketone, 2,2′-Dimethoxy-1,2-diphenylethan-1-one, 2-Methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-Benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-Hydroxy-2-methyl-1-phenylpropan-1-one, 2, 4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-benzoyl-4'-methyldimethylsulfide, 2,2'-diethoxyacetophenone, benzyl dimethylketal, benzyl-β-methoxyethyl acetal, o-benzoyl methyl benzoate, bis(4-dimethylaminophenyl)ketone, p-dimethylaminoacetophenone, α,α-dichloro-4-phenoxyacetophenone, pentyl-4-dimethylaminobenzoate, 2-(o-chlorophenyl)-4,5-diphenylimidazoline dimer, 2,4-bis-trichloromethyl-6-[di-(ethoxycarbonylmethyl)amino]phenyl-S-triazine, 2,4-bis-trichloromethyl-6-(4-ethoxy)phenyl-S-triazine, 2,4-bis-trichloromethyl-6-(3-bromo-4-ethoxy)phenyl-S-triazineanthraquinone, 2-t-butylanthraquinone, 2-amyl anthraquinone, β-chloroanthraquinone, etc. These photopolymerization initiators may be used alone or in combination of two or more kinds.

[0047] Among photopolymerization initiators, it is preferable to use one or a mixture of two or more selected from the group consisting of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, thioxanthone and thioxanthone derivatives, 2,2'-dimethoxy-1,2-diphenylethan-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-1-propanone, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, because it shows activity over a wider range of wavelengths of light and provides a highly curable coating material.

[0048] Commercially available photopolymerization initiators include, for example, "Irgacure-184", "Irgacure-149", "Irgacure-261", "Irgacure-369", "Irgacure-500", "Irgacure-651", "Irgacure-754", "Irgacure-784", "Irgacure-819", "Irgacure-907", "Irgacure-1116", "Irgacure-1664", "Irgacure-1700", "Irgacure-1800", "Irgacure-1850", "Irgacure-2959", and "Irgacure-3000". -4043", "Darocur-1173", "Lucirin TPO" manufactured by BASF, "Kayacure-DETX", "Kayacure-MBP", "Kayacure-DMBI", "Kayacure-EPA", "Kayacure-OA" manufactured by Nippon Kayaku Co., Ltd., "Vicure-10" and "Vicure-55" manufactured by Stouffer Chemical, "Trigonal P1" manufactured by Akzo, "Sandoz" manufactured by Sandray 1000, "Deep" manufactured by Upjohn, and "Quantacure-PDO", "Quantacure-ITX", and "Quantacure-EPD" manufactured by Ward Blenkinsop.

[0049] The content of the photopolymerization initiator is preferably within a range in which the photopolymerization initiator can fully exhibit its function and does not cause crystal precipitation or deterioration of the coating film properties. Specifically, the photopolymerization initiator is preferably used in an amount of 0.05 to 10 mass % relative to the total amount of the active energy ray-curable resin composition, and more preferably in an amount of 0.1 to 5 mass %.

[0050] The active energy ray-curable resin composition of the present invention may further contain various photosensitizers in combination with the photopolymerization initiator. Examples of the photosensitizer include amines, ureas, sulfur-containing compounds, phosphorus-containing compounds, chlorine-containing compounds, nitriles, and other nitrogen-containing compounds.

[0051] The active energy ray curable resin composition of the present invention may further use a thermal polymerization initiator. Examples of the thermal polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-(2,4-dimethylvaleronitrile), and 2,2'-azobis-(4-methoxy-2,4-dimethylvaleronitrile); organic peroxides such as benzoyl peroxide, lauroyl peroxide, t-butyl peroxy pivalate, t-butyl peroxy ethylhexanoate, 1,1'-bis-(t-butylperoxy)cyclohexane, t-amyl peroxy-2-ethylhexanoate, and t-hexyl peroxy-2-ethylhexanoate, and hydrogen peroxide, and it is preferable to use the initiator in an amount of 0.05 to 20 parts by mass relative to 100 parts by mass of the resin composition.

[0052] The active energy ray-curable resin composition of the present invention may contain various blending materials for the purpose of adjusting the viscosity or refractive index, or adjusting the color tone of the coating film, or adjusting other paint properties or coating film physical properties, for example, various resins such as the above-mentioned organic solvents, acrylic resins, phenolic resins, polyester resins, polystyrene resins, urethane resins, urea resins, melamine resins, alkyd resins, epoxy resins, polyamide resins, polycarbonate resins, petroleum resins, and fluororesins, various organic or inorganic particles such as PTFE (polytetrafluoroethylene), polyethylene, polypropylene, carbon, titanium oxide, alumina, copper, and silica fine particles, polymerization initiators, polymerization inhibitors, antistatic agents, defoamers, viscosity modifiers, light resistance stabilizers, weather resistance stabilizers, heat resistance stabilizers, antioxidants, rust inhibitors, slip agents, waxes, gloss modifiers, release agents, compatibilizers, conductivity modifiers, pigments, dyes, dispersants, dispersion stabilizers, silicone-based, and hydrocarbon-based surfactants.

[0053] The active energy ray curable resin composition of the present invention can be obtained by appropriately adding the above-mentioned three-dimensional crosslinked structure, a polyfunctional vinyl compound, a photopolymerization initiator, an organic solvent, etc. to prepare a mixed solution. The coating material of the present invention contains the above-mentioned active energy ray curable resin composition, and can be suitably used in particular as a coating material for hard coat.

[0054] [Paint film] The coating film of the present invention is a cured product of the active energy ray curable resin composition. The coating film can be obtained, for example, by stirring a mixed solution containing the three-dimensional crosslinked structure, a polyfunctional vinyl compound, a photopolymerization initiator, an organic solvent, etc., applying the mixed solution to a substrate such as a PET film, and irradiating the mixed solution with active energy rays such as ultraviolet rays. The mixed solution can be semi-cured by irradiating the mixed solution with active energy rays such as ultraviolet rays until the mixed solution has a viscosity suitable for coating, and then completely cured by irradiating the mixed solution with active energy rays again after coating. The coating film of the present invention is particularly useful as a hard coat coating film.

[0055] [lens] The lens of the present invention is a cured product of the active energy ray curable resin composition. The lens can be obtained by, for example, injecting the active energy ray curable resin composition into a mold such as a die, and curing and molding it by irradiating with active energy rays. The lens of the present invention is particularly useful as an optical lens. The active energy rays refer to ionizing radiation such as ultraviolet rays, electron beams, α rays, β rays, and γ rays.

[0056] The active energy ray-curable resin composition of the present invention has small molding shrinkage in a cured coating film (particularly a hard coat coating film) and has good flexibility and scratch resistance, and is therefore suitable for hard coats for electronic devices such as smartphones and tablet terminals, and optical lenses (e.g., flash lenses, Fresnel lenses, and telephoto lenses) mounted on smartphones, digital cameras, and the like. EXAMPLES

[0057] The present invention will be described in more detail below with reference to specific manufacturing examples and examples, but the present invention is not limited to these examples. The three-dimensional crosslinked structures of the present invention into which acrylic groups have been introduced were produced by the following method, and the viscosity and gel particle size were measured. Furthermore, the three-dimensional crosslinked structures were crosslinked and applied to a film, and the hardened coating film was subjected to a steel wool (SW) test. Table 1 shows the resin composition, molecular weight of the linear polymer (straight-chain polymer), gel particle size, viscosity, and steel wool (SW) test results for each of the three-dimensional crosslinked structures.

[0058] [Molecular weight-GPC measurement] In the examples of the present invention, the number average molecular weight (Mn) and the weight average molecular weight (Mw) are values ​​measured using a gel permeation chromatograph (GPC) under the following conditions. Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: Tosoh Corporation guard column HXL-H + Tosoh Corporation TSKgel G5000HXL + Tosoh Corporation TSKgel G4000HXL +Tosoh Corporation TSKgel G3000HXL + Tosoh Corporation TSKgel G2000HXL Detector: RI (differential refractometer) Data processing: Tosoh Corporation SC-8010 Measurement conditions: Column temperature 40℃ Solvent Tetrahydrofuran Flow rate 1.0ml / min Standard: Polystyrene Sample: 100 μl of tetrahydrofuran solution containing 0.5% by mass of resin solids filtered through a microfilter

[0059] [Gel particle size measurement] A 1% by mass tetrahydrofuran solution was prepared for the three-dimensional crosslinked structure with acrylic groups introduced therein, calculated as a resin solid content, and the average particle size (D50) was evaluated using a dynamic light scattering particle size distribution analyzer LB-500 (manufactured by Horiba, Ltd.).

[0060] [Viscosity-EMS measurement] A polymer solution of 40% by mass, calculated as resin solid content, was prepared for the three-dimensional crosslinked structure into which acrylic groups had been introduced. A dedicated glass tube and a φ2.0 mm spherical probe were placed in this solution and sealed. The viscosity of this solution was measured at 23°C using a non-contact viscosity measuring device EMS-1000 (Kyoto Electronics Manufacturing Co., Ltd.) at the rotation speed of the probe. The coatability was evaluated according to the following criteria based on the viscosity value. ○ (Good): Viscosity = less than 1000 mPa s × (bad): Viscosity = 1000 mPa s or more

[0061] [Abrasion resistance - Steel wool (SW) test] Using a reciprocating abrasion tester TYPE 30S (manufactured by Shinto Scientific Co., Ltd.), a disk-shaped indenter was wrapped in 0.5 g of steel wool ("Bonstar #0000" manufactured by Japan Steel Wool Co., Ltd.), and a load of 500 g was applied to the indenter, which was then reciprocated 100 times over the coating surface of the film. The haze value of the coating before and after the test was measured using a "Haze Computer HZ-2" manufactured by Suga Test Instruments Co., Ltd., and the abrasion resistance was evaluated from the ΔH value according to the following criteria. ○ (Good): δH value = less than 10 × (bad): δH value = 10 or more

[0062] [Example 1] First, 45 parts by mass of methyl ethyl ketone, 20.6 parts by mass of methyl methacrylate (MMA), 20.6 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 3.8 parts by mass of 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid, and 0.35 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged into a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 18 hours to obtain a linear acrylic resin (MMA / HEMA=50 / 50) with a number average molecular weight of 5,500 and a weight average molecular weight of 6,400 as a linear polymer. Next, 18 parts by mass of the obtained linear acrylic resin, 583 parts by mass of methyl ethyl ethene, 0.20 parts by mass of 2,2'-azobis(2-methylbutyronitrile), and 6.9 parts by mass of ethylene glycol dimethacrylate (EGDMA) were added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to deoxygenate. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 18 hours, obtaining a polymer with a number average molecular weight of 19,100 and a weight average molecular weight of 25,800 as a three-dimensional crosslinked structure having hydroxyl groups. Then, 25 parts by mass of the obtained three-dimensional crosslinked structure (a methyl ethyl ketone solution with a solid content of 40.4% by mass), 3.5 parts by mass of 2-isocyanatoethyl acrylate (AOI, manufactured by Showa Denko K.K.), 0.0041 parts by mass of Neostan U-28 (manufactured by Nitto Kasei K.K.), 0.0041 parts by mass of methoquinone, and 0.041 parts by mass of dibutylhydroxytoluene (BHT) were added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube. Thereafter, the temperature in the system was raised to 80°C while stirring under an air stream, and the mixture was reacted at 80°C for 4 hours to obtain a polymer having a number average molecular weight of 9,800 and a weight average molecular weight of 17,500 as a three-dimensional crosslinked structure having an acrylic group introduced therein. The viscosity and gel particle size were measured by the above-mentioned method using this three-dimensional crosslinked structure solution. A mixed solution was prepared by mixing 75 parts by mass of the obtained 3D crosslinked structure with acrylic groups introduced, 25 parts by mass of Aronix M-404 (DPHA, manufactured by Toa Gosei Co., Ltd.), 0.1 parts by mass of BYK-3505 (manufactured by BYK Japan Co., Ltd.), 4 parts by mass of 1-hydroxy-cyclohexyl-phenyl-ketone (trade name "Irgacure 184", manufactured by Chiba Specialty Chemicals Co., Ltd.), and 233 parts by mass of methyl ethyl ethene. This solution was applied to a PET film with a thickness of 5 μm, and then cured with an ultraviolet irradiation device CSOT-40 (manufactured by GS Yuasa Co., Ltd.) to obtain a coating film. A steel wool test was performed using the above method using a test piece with a coating film formed on this PET film.

[0063] [Example 2] First, 45 parts by mass of methyl ethyl ketone, 16.5 parts by mass of methyl methacrylate (MMA), 24.7 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 3.8 parts by mass of 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid, and 0.35 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged into a four-neck flask equipped with a stirrer, a cooling tube, and a dropping funnel and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 18 hours to obtain a linear acrylic resin (MMA / HEMA=40 / 60) with a number average molecular weight of 5,200 and a weight average molecular weight of 6,000 as a linear polymer. Next, 18 parts by mass of the obtained linear acrylic resin, 592 parts by mass of methyl ethyl ethene, 0.19 parts by mass of 2,2'-azobis(2-methylbutyronitrile), and 6.5 parts by mass of ethylene glycol dimethacrylate (EGDMA) were added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to deoxygenate. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 18 hours, obtaining a polymer with a number average molecular weight of 17,500 and a weight average molecular weight of 23,900 as a three-dimensional crosslinked structure having hydroxyl groups. Then, 25 parts by mass of the obtained three-dimensional crosslinked structure (methyl ethyl ketone solution with a solid content of 41.3% by mass) was added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and 4.4 parts by mass of 2-isocyanatoethyl acrylate (AOI, manufactured by Showa Denko K.K.), 0.0044 parts by mass of Neostan U-28 (manufactured by Nitto Kasei K.K.), 0.0059 parts by mass of methoquinone, and 0.044 parts by mass of dibutylhydroxytoluene (BHT) were added. After that, the temperature in the system was raised to 80°C while stirring under an air flow, and the reaction was carried out at 80°C for 4 hours to obtain a polymer having a number average molecular weight of 8,700 and a weight average molecular weight of 15,900 as a three-dimensional crosslinked structure into which an acrylic group was introduced. The viscosity and gel particle size were measured by the above-mentioned method using this three-dimensional crosslinked structure solution. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0064] [Example 3] First, 3.2 parts by mass of ethanol, 11 parts by mass of methyl ethyl ketone, 17.6 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 4.1 parts by mass of 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid, and 0.28 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged into a four-neck flask equipped with a stirrer, a cooling tube, and a dropping funnel, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 16 hours to polymerize poly2-hydroxyethyl methacrylate (HEMA). After cooling to room temperature, 18 parts by mass of methyl ethyl ketone, 26.4 parts by mass of methyl methacrylate (MMA), and 0.28 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. The temperature in the system was then raised to 70°C with stirring, and the reaction was carried out at 70°C for 16 hours to obtain a linear blocked acrylic resin (HEMA-b-MMA=40 / 60) with a number average molecular weight of 5,200 and a weight average molecular weight of 5,800 as a linear polymer. Next, 12 parts by mass of the obtained linear acrylic resin, 382 parts by mass of methyl ethyl ethene, 0.13 parts by mass of 2,2'-azobis(2-methylbutyronitrile), and 4.4 parts by mass of ethylene glycol dimethacrylate (EGDMA) were added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to deoxygenate. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 18 hours, obtaining a polymer with a number average molecular weight of 27,400 and a weight average molecular weight of 39,200 as a three-dimensional crosslinked structure having hydroxyl groups. Then, 27 parts by mass of the obtained three-dimensional crosslinked structure (methyl ethyl ketone solution with a solid content of 37.4% by mass), 2.9 parts by mass of 2-isocyanatoethyl acrylate (AOI, manufactured by Showa Denko K.K.), 0.0039 parts by mass of Neostan U-28 (manufactured by Nitto Kasei K.K.), 0.0052 parts by mass of methoquinone, and 0.039 parts by mass of dibutylhydroxytoluene (BHT) were added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube. Thereafter, the temperature in the system was raised to 80°C while stirring under an air stream, and the mixture was reacted at 80°C for 4 hours to obtain a polymer having a number average molecular weight of 18,000 and a weight average molecular weight of 38,600 as a three-dimensional crosslinked structure having an acrylic group introduced therein. The viscosity and gel particle size were measured by the above-mentioned method using this three-dimensional crosslinked structure solution. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0065] [Example 4] First, 4.8 parts by mass of ethanol, 8.5 parts by mass of methyl ethyl ketone, 18.4 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 2 parts by mass of 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid, and 0.14 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged into a four-neck flask equipped with a stirrer, a cooling tube, and a dropping funnel and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 16 hours to polymerize poly2-hydroxyethyl methacrylate. After cooling to room temperature, 18.7 parts by mass of methyl ethyl ketone, 27.6 parts by mass of methyl methacrylate (MMA), and 0.14 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 16 hours, and a linear blocked acrylic resin (HEMA-b-MMA = 40 / 60) with a number average molecular weight of 8,600 and a weight average molecular weight of 9,400 was obtained as a linear polymer. Next, 12 parts by mass of the obtained linear acrylic resin, 339 parts by mass of methyl ethyl ethene, 0.08 parts by mass of 2,2'-azobis(2-methylbutyronitrile), and 2.7 parts by mass of ethylene glycol dimethacrylate were added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to deoxygenate. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 18 hours to obtain a three-dimensional crosslinked structure having a number average molecular weight of 34,000 and a weight average molecular weight of 46,700 as a three-dimensional crosslinked structure having hydroxyl groups. Then, 25 parts by mass of the obtained three-dimensional crosslinked structure (a methyl ethyl ketone solution with a solid content of 31.7% by mass) was added to a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and 2.6 parts by mass of 2-isocyanatoethyl acrylate (AOI, manufactured by Showa Denko K.K.), 0.0032 parts by mass of Neostan U-28 (manufactured by Nitto Kasei K.K.), 0.0043 parts by mass of methoquinone, and 0.032 parts by mass of dibutylhydroxytoluene (BHT) were added. After that, the temperature in the system was raised to 80°C while stirring under an air flow, and the reaction was carried out at 80°C for 4 hours to obtain a polymer having a number average molecular weight of 26,200 and a weight average molecular weight of 61,200 as a three-dimensional crosslinked structure into which an acrylic group was introduced. The viscosity and gel particle size were measured by the above method using this three-dimensional crosslinked structure solution. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0066] [Example 5] First, 20.0 parts by mass of methyl ethyl ketone, 4.1 parts by mass of 4-cyano-4-(dodecylsulfanylthiocarbonyl)sulfanylpentanoic acid, 26.4 parts by mass of methyl methacrylate (MMA), and 0.19 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged into a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 16 hours to polymerize polymethyl methacrylate. After cooling to room temperature, 3.2 parts by mass of ethanol, 8.8 parts by mass of methyl ethyl ketone, 17.6 parts by mass of 2-hydroxyethyl methacrylate (HEMA), and 0.19 parts by mass of 2,2'-azobis(2-methylbutyronitrile) were charged, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 16 hours, and a linear blocked acrylic resin (MMA-b-HEMA = 40 / 60) with a number average molecular weight of 5,400 and a weight average molecular weight of 5,900 was obtained as a linear polymer. In a four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube, 18 parts by mass of the obtained linear acrylic resin, 555 parts by mass of methyl ethyl ethene, 0.10 parts by mass of 2,2'-azobis(2-methylbutyronitrile), and 6.2 parts by mass of ethylene glycol dimethacrylate (EGDMA) were added, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. After that, the temperature in the system was raised to 70°C while stirring, and the reaction was carried out at 70°C for 18 hours, and a three-dimensional crosslinked structure having a number average molecular weight of 25,100 and a weight average molecular weight of 33,400 was obtained as a three-dimensional crosslinked structure having hydroxyl groups. Then, 28 parts by mass of the obtained three-dimensional crosslinked structure (a methyl ethyl ketone solution with a solid content of 43.0% by mass), 3.5 parts by mass of 2-isocyanatoethyl acrylate (AOI, manufactured by Showa Denko K.K.), 0.0047 parts by mass of Neostan U-28 (manufactured by Nitto Kasei K.K.), 0.0062 parts by mass of methoquinone, and 0.047 parts by mass of dibutylhydroxytoluene (BHT) were added to a four-neck flask equipped with a stirring device, a cooling tube, a dropping funnel, and a nitrogen inlet tube. Thereafter, the temperature in the system was raised to 80°C while stirring under an air stream, and the mixture was reacted at 80°C for 4 hours to obtain a polymer having a number average molecular weight of 19,700 and a weight average molecular weight of 37,800 as a three-dimensional crosslinked structure having an acrylic group introduced therein. The viscosity and gel particle size were measured by the above method using this three-dimensional crosslinked structure solution. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0067] [Comparative Example 1] A four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube was charged with 154 parts by mass of methyl isobutyl ketone, and the temperature in the system was raised with stirring until it reached 110°C. A mixture of 200 parts by mass of glycidyl methacrylate and 300 parts by mass of methyl methacrylate, and a mixture of 90 parts by mass of methyl isobutyl ketone and 10 parts by mass of t-butylperoxy-2-ethylhexanoate ("Perbutyl O" manufactured by NOF Corporation) were added dropwise from the dropping funnel over a period of 4 hours, and the temperature was then maintained at 110°C for 18 hours. After that, the temperature was lowered to 80° C., and then 1.8 parts by mass of dibutylhydroxytoluene (BHT), 0.3 parts by mass of methoquinone, and 103 parts by mass of acrylic acid (AA) were charged, followed by the addition of 3 parts by mass of triphenylphosphine, and the temperature was further raised to 105° C., and it was confirmed that the acid value was 5 mgKOH / g or less, yielding a polymer with a number average molecular weight of 14,900 and a weight average molecular weight of 30,300. The viscosity of the solution of this polymer was measured by the method described above. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0068] [Comparative Example 2] A four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube was charged with 154 parts by mass of methyl isobutyl ketone, and the temperature in the system was raised with stirring until it reached 110°C. A mixed liquid of 300 parts by mass of glycidyl methacrylate and 200 parts by mass of methyl methacrylate, and a mixed liquid of 90 parts by mass of methyl isobutyl ketone and 10 parts by mass of t-butylperoxy-2-ethylhexanoate ("Perbutyl O" manufactured by NOF Corporation) were added dropwise from the dropping funnel over a period of 4 hours, and the temperature was then maintained at 110°C for 18 hours. After that, the temperature was lowered to 80°C, and then 1.8 parts by mass of dibutylhydroxytoluene (BHT), 0.3 parts by mass of methoquinone, and 154 parts by mass of acrylic acid (AA) were added, and 3 parts by mass of triphenylphosphine was added. The temperature was further raised to 105°C, and it was confirmed that the acid value was 5 mgKOH / g or less, and a polymer with a number average molecular weight of 12,100 and a weight average molecular weight of 34,700 was obtained. An acrylic acrylate having the following structure was obtained. The viscosity of this acrylic resin was measured by the above method. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0069] [Comparative Example 3] A four-neck flask equipped with a stirrer, a cooling tube, a dropping funnel, and a nitrogen inlet tube was charged with 154 parts by mass of methyl isobutyl ketone, and the temperature in the system was raised with stirring until it reached 110°C. A mixture of 400 parts by mass of glycidyl methacrylate and 100 parts by mass of methyl methacrylate, and a mixture of 90 parts by mass of methyl isobutyl ketone and 10 parts by mass of t-butylperoxy-2-ethylhexanoate ("Perbutyl O" manufactured by NOF Corporation) were added dropwise from the drop funnel over a period of 4 hours, and the temperature was then maintained at 110°C for 18 hours. After that, the temperature was lowered to 80° C., and then 1.8 parts by mass of dibutylhydroxytoluene (BHT), 0.3 parts by mass of methoquinone, and 205 parts by mass of acrylic acid (AA) were charged, followed by the addition of 3 parts by mass of triphenylphosphine, and the temperature was further raised to 105° C., and it was confirmed that the acid value was 5 mgKOH / g or less, yielding a polymer with a number average molecular weight of 14,200 and a weight average molecular weight of 41,900. The viscosity of the solution of this polymer was measured by the method described above. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0070] [Comparative Example 4] A four-neck flask equipped with a stirring device, a cooling tube, and a nitrogen inlet tube was replaced with nitrogen, and 400 parts by mass of methyl isobutyl ketone, 237 parts by mass of glycidyl methacrylate, and 356 parts by mass of methyl methacrylate were charged as a solvent, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. The temperature was raised to 40°C while stirring under a nitrogen stream. Next, 10.9 parts by mass of 2,2'-bipyridyl and 3.5 parts by mass of cuprous chloride were charged, and the flask was stirred for 30 minutes while maintaining the temperature at 40°C. Then, 6.8 parts by mass of ethyl 2-bromoisobutyrate was added, and the reaction was carried out for 6 hours at 40°C under a nitrogen stream. In order to remove the catalyst, the resulting reaction product was diluted with methyl ethyl ketone, an ion exchange resin was added, and the mixture was stirred for 1 hour. This was filtered through an ion exchange resin to obtain a linear acrylic resin (HEMA / MMA=40 / 60) solution. Further, after lowering the temperature of the solution containing this linear acrylic resin to 80°C, 1.8 parts by mass of dibutylhydroxytoluene (BHT), 0.3 parts by mass of methoquinone, and 121 parts by mass of acrylic acid (AA) were charged, and then 3 parts by mass of triphenylphosphine were added, and the temperature was further raised to 105°C, and it was confirmed that the acid value was 5 mgKOH / g or less, and a linear acrylic resin with a narrow molecular weight distribution was obtained. The molecular weight of this resin was measured by GPC, and the number average molecular weight (Mn) was 26,800 and the weight average molecular weight (Mw) was 37,600. The viscosity of the solution containing this acrylic resin was measured by the above method. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0071] [Comparative Example 5] A four-neck flask equipped with a stirring device, a cooling tube, and a nitrogen inlet tube was replaced with nitrogen, and 400 parts by mass of methyl isobutyl ketone and 237 parts by mass of glycidyl methacrylate were charged as a solvent, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. The temperature was raised to 40°C while stirring under a nitrogen stream. Next, 10.9 parts by mass of 2,2'-bipyridyl and 3.5 parts by mass of cuprous chloride were charged, and the flask was stirred for 30 minutes while maintaining the temperature at 40°C. Then, 6.8 parts by mass of ethyl 2-bromoisobutyrate was added, and the reaction was carried out for 4 hours at 40°C under a nitrogen stream to obtain polyglycidyl methacrylate. 356 parts by mass of methyl methacrylate, which had been deoxygenated by introducing nitrogen in advance, was charged into this reaction liquid. The reaction was carried out for 4 hours at 40°C under a nitrogen stream. In order to remove the catalyst, the resulting reaction product was diluted with methyl ethyl ketone, ion exchange resin was added, and the mixture was stirred for 1 hour. After filtering the ion exchange resin, a linear blocked acrylic resin (HEMA-b-MMA=40 / 60) solution was obtained. The temperature of this acrylic resin solution was further lowered to 80°C, and then 1.8 parts by mass of dibutylhydroxytoluene (BHT), 0.3 parts by mass of methoquinone, and 121 parts by mass of acrylic acid (AA) were added, followed by adding 3 parts by mass of triphenylphosphine, and the temperature was further raised to 105°C. The acid value was confirmed to be 5 mgKOH / g or less, and a linear acrylic resin with a narrow molecular weight distribution was obtained. The molecular weight of this resin was measured by GPC, and the number average molecular weight (Mn) was 23,300 and the weight average molecular weight (Mw) was 39,000. The viscosity of this acrylic resin was measured by the above method. Thereafter, a test piece for a steel wool test was prepared in the same manner as in Example 1, and a steel wool test was carried out.

[0072] [Comparative Example 6] A four-neck flask equipped with a stirring device, a cooling tube, and a nitrogen inlet tube was replaced with nitrogen, and 400 parts by mass of methyl ethyl ketone, 237 parts by mass of glycidyl methacrylate, and 356 parts by mass of methyl methacrylate were charged as a solvent, and nitrogen was introduced at room temperature for 1 hour to perform deoxygenation. The temperature was raised to 40°C while stirring under a nitrogen stream. Next, 43.6 parts by mass of 2,2'-bipyridyl and 14 parts by mass of cuprous chloride were charged, and the flask was stirred for 30 minutes while maintaining the temperature at 40°C. Then, 27.2 parts by mass of ethyl 2-bromoisobutyrate was added, and the mixture was reacted for 6 hours at 40°C under a nitrogen stream to obtain a linear polymer. The molecular weight of this linear polymer was measured by GPC, and the number average molecular weight (Mn) was 6,800 and the number average molecular weight (Mw) was 7,700. Next, 2000 parts by mass of methyl ethyl ketone and 6.2 parts by mass of ethylene glycol dimethacrylate (EGDMA) that had been deoxygenated in advance were added, and the mixture was reacted at 50°C for 18 hours. To remove the catalyst, the reaction mixture was diluted with methyl ethyl ketone, ion exchange resin was added, and the mixture was stirred for 1 hour. After filtering the ion exchange resin, a three-dimensional crosslinked structure with epoxy groups was obtained. The three-dimensional crosslinked structure solution was partially desolvated using an evaporator to obtain a methyl ethyl ketone solution of a three-dimensional crosslinked structure having an epoxy group with a solid content of 55 mass %. In a four-neck flask equipped with a stirrer, a cooling tube, and an oxygen inlet tube, 1200 parts by mass of this three-dimensional crosslinked structure methyl ethyl ketone solution, 1.8 parts by mass of dibutylhydroxytoluene (BHT), 0.3 parts by mass of methoquinone, and 121 parts by mass of acrylic acid (AA) were charged, and then 3 parts by mass of triphenylphosphine were added and the temperature was further raised to 105°C. After 4 hours at 105°C, the inside of the flask solidified due to gelation before the acid value became 5 mgKOH / g or less. Therefore, evaluation was not possible (ND).

[0073] [Table 1]

[0074] In Comparative Example 1-3, a linear polymer having a conventional acrylic group by epoxy group-acrylic acid addition obtained by conventional free radical polymerization was used. In Comparative Examples 4 and 5, a linear polymer having an acrylic group by epoxy group-acrylic acid addition copolymerized or blocked by controlled radical polymerization was used. In Comparative Example 6, an attempt was made to prepare a three-dimensional crosslinked structure having an acrylic group by epoxy group-acrylic acid addition, but the solution was completely gelled due to an unintended crosslinking reaction of epoxy group-acrylic acid, and the intended three-dimensional crosslinked structure could not be prepared. On the other hand, in Examples 1 to 5, the particle diameter of the three-dimensional crosslinked structure is very small at about 10 nm, and the viscosity is lower than that of Comparative Example 1-5. Therefore, it can be used as a hard coating agent even with a small amount of solvent. It can also be seen that the coating film obtained from the three-dimensional crosslinked structure of Examples 1 to 5 has good abrasion resistance and excellent hard coating properties.

Claims

1. A method for producing a three-dimensional crosslinked structure having a number average molecular weight (Mn) of 5,000 to 300,000, comprising the steps of: polymerizing a linear polymer having a number average molecular weight (Mn) in the range of 1,000 to 200,000, which is a copolymer or block polymer of a (meth)acrylic compound having no active hydrogen functional group and a (meth)acrylic compound having an active hydrogen functional group which is a hydroxyl group, a carboxyl group or an amino group; chemically bonding one end of a plurality of said linear polymers to form a core portion; and converting the active hydrogen functional groups, which are hydroxyl groups, carboxyl groups or amino groups, of said linear polymer into (meth)acrylic groups.

2. The method for producing a three-dimensional crosslinked structure according to claim 1 , wherein one end of the linear polymer is a halogen group or a functional group containing a thiocarbonylthio structure.

3. A method for producing a three-dimensional crosslinked structure according to claim 1 or 2, wherein the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of the three-dimensional crosslinked structure is 1.1 to 3.

0.

4. A method for producing an active energy ray-curable resin composition, using the three-dimensional crosslinked structure obtained according to any one of claims 1 to 3.

5. A method for producing a cured product, comprising curing the active energy ray-curable resin composition according to claim 4.

Citation Information

Patent Citations

  • Novel silicone-containing polymers and oxygen-permeable contact lenses

    JP1993506687A

  • Novel silicone-containing polymers and oxygen-permeable hydrophilic contact lenses from said polymers

    JP1994503103A

  • Active energy ray curable resin composition and film substrate

    JP2011207947A

  • Curable resin composition including crosslinkable particles

    WO2016199717A1